Analysis of Radial Excitations of Octet Baryons in QCD Sum Rules. (3rd January 2017) - Aliev, T. M.; Bilmis, S.
Abstract : Using the QCD sum rules method, we estimate the mass and residues of the first radial excitations of octet baryons. The contributions coming from the ground state baryons are eliminated by constructing the linear combinations of the sum rules corresponding to different Lorentz structures. Our predictions of the masses of the first radial excitations of octet baryons are in good agreement with the data.